A 0.31-1 GHz Fast-Corrected Duty-Cycle Corrector With Successive Approximation Register for DDR DRAM Applications - MIN, Young-Jae; JEONG, Chan-Hui; KIM, Kyu-Young; WON HO CHOI; SON, Jong-Pil; KIM, Chulwoo; KIM, Soo-Won (IEEE transactions on very large scale integration (VLSI) systems, 2012)
This brief presents a duty cycle corrector (DCC) using a binary search algorithm with successive approximation register (SAR). The proposed DCC consists of a duty-cycle detector, a duty-cycle adjuster, its controller and an output buffer. In order to achieve fast duty-correction with a small die area, a SAR-controller is exploited as a duty-correction controller. The proposed DCC circuit has been implemented and fabricated in a 0.13-μm CMOS process and occupies 0.048 mm 2 . The measured duty-cycle error for the 50% duty-rate is below 1% (or 10 pS) within 320 pS external input duty-cycle error. The duty of output signal is corrected only with 14 cycles. This DCC operates from 312.5 MHz to 1 GHz and dissipates 3.2 mW at 1 GHz.